Optimization of the order and spacing of sequences in an MRI exam to reduce the maximum temperature and thermal dose - Carluccio, Giuseppe (Magn Reson Med, 2018)
PURPOSE: Evaluate the possibility to reduce specific energy absorption rate (SAR)-induced maximum temperature and thermal dose by rearranging the order and spacing of sequences without increasing duration of the MRI examination. METHODS: Using numerical simulations based on an actual SAR-intensive MRI examination, optimizations to reduce either maximum temperature or thermal dose were performed. For each permutation of groups of sequences having the same patient table position, temperature and thermal dose were computed very rapidly using recently published methods. Disposition of sequences was further adjusted by optimizing the spacing between each sequence without exceeding the original exam duration. RESULTS: The maximum simulated temperature in the original exam was 42.38°C, and the maximum thermal dose was 3.23 cumulative effective minutes at 43°C (CEM43). After optimization to reduce maximum temperature, it was 41.77°C, and after optimization to minimize the thermal dose, it was 1.42 CEM43. CONCLUSION: It is possible to reduce maximum temperature and thermal dose in the exam by changing the arrangement and spacing of the sequences without increasing the duration of the exam (by increasing TR or adding delays) or compromising image quality (by reducing flip angles).